Exploring the 'active mechanisms' for engaging rural-dwelling older men with dementia in a community technological initiative. Issue 9 (5th September 2020) - Hicks, Ben; Innes, Anthea; Nyman, Samuel R.
Abstract: Research has suggested ecopsychosocial initiatives can promote a sense of wellbeing and inclusion in people with dementia. However, few studies have elucidated the 'active mechanisms' whereby such initiatives can achieve these outcomes, so hindering their generalisability. This is particularly pertinent when seeking to support community-dwelling older men with dementia who are reluctant to engage with traditional health and social care initiatives. This paper reports on a study that drew from the principles of Participatory Action Research to explore the 'active mechanisms' of a technological initiative for older men (65+ years) with dementia in rural England. An individually tailored, male-only initiative, using off-the-shelf computer game technology ( e.g. iPad, Nintendo Wii and Microsoft Kinect) was delivered over a nine-week period. Multiple qualitative methods were employed, including: focus groups, open interviews and extensive reflective field notes, to gather data from the perspective of 22 men, 15 care partners and five community volunteers. The data were analysed thematically and interpreted using a masculinity lens. Three mechanisms contributed to the initiative's success: the use of the technology, the male-only environment and the empowering approach adopted. The paper argues that initiatives aimed at community-dwelling older men with dementia would be advised to consider these gendered experiences and ensure participants can maximise their masculine capital when participating in them, by providing enabling activities, non-threatening environments and empowering approaches of delivery.